MICROSCOPIC SIMULATI ON OF ROAD TRANSPORT ON THE SECTION BYTČA RUŽOMBEROK (Perner's Contacts, 2016)
Due to the constantly changing demands of road users, it is necessary to create transport infrastructure which will be able to meet these demands and introduce organising measurements to help achieve the effective use of transport infrastructure. In our paper we focused on simulation of traffic situation on road network between city of Bytča and Ružomberok, where congestions and traffic accidents often occur. This section is one of the most loaded sections of road network in the Slovak Republic.
Keywords: simulation; safety; traffic accident rate; model